ASSOCIATION OF CHANGES MAGNESIUM AND CHLORIDE LEVELS TO MUSCLE STRENGTH FOR PRE AND POST REGULAR HEMODIALYSIS PATIENTS - Ratna Tri Riskiana, Radar Radius Tarigan & Sumi Ramadhani (International Journal of Research Science and Management, 2020)
Introduction. One of the functions of the kidneys is as excretion function, especially electrolytes such as magnesium and chloride. Magnesium functions as a protein metabolism as well as the synthesis of mitochondrial ATP and has an important role in catalyzing more than 300 enzymatic reactions in the human body including protein synthesis, nerve and muscle transmission, and neuromuscular conduction. Chloride's function is currently unclear, but it can be identified that apart from being an acid-base balance and gastric acid, chloride is also important as a potential development of the membrane in muscle fibers. Regular hemodialysis patients always complain of muscle weakness which can be caused by muscle atrophy, muscle myopathy, reduced activity or a combination. Compared with normal patients muscle strength in regular hemodialysis patients can occur weakness Method. This study is analytical with a cross-sectional retrospective design. Data were analyzed after distribution test, then mean difference and correlation test was using the SPPS program where p <0.05 was considered statistically significant. Results. This study showed not significantly for Magnesium and Chloride with muscle strength in Patients with Regular Hemodialysis. Conclusion. Not significant association of changes Magnesium and Chloride levels to Muscle Strength for Pre and Post Regular Hemodialysis patients.